Woven, Not Carved: The Pangnirtung Tapestries are Northern Art with Global Appeal - Cross, L.D. (ARCTIC, 2003)
. In an attempt to ameliorate the negative effects of relocations and to create an economic base, the government funded arts and crafts initiatives across the Arctic. One such project was a weaving studio in Pangnirtung on Baffin Island, now in the Territory of Nunavut (meaning 'our land'). There, from 1969 to 1972, Ontario textile and silver/goldsmith artist Donald Stuart, supported by the federal government and the Canadian Guild of Crafts in Montreal, initiated a weaving project for a small group of young Inuit women. Already skilled in knitting and sewing wind- and water-resistant garments, they quickly mastered hand-weaving techniques. Today, this initiative has become the largest hand-weaving studio in Canada, and Stuart has returned on many occasions as friend and advisor. . The ancient skills used to create smooth-finish, flat-weave rugs and tapestries are now used by trained Inuit weavers to translate drawings by local artists into fibre art. Their blending of craftsmanship with local images expresses unique cultural values, . Although initiated by outsiders, Inuit tapestry art has captured the essence of northern life and cultural values in a way that speaks directly to people from many nations. As Inuit weavers continue to develop their tapestry art, new styles and new subjects will evolve. Who knows where their adaptability and collective creative spirit will take them in the next 30 years?